The challenges of Leading Remote Teams and its influence on Strategies for Success - Taha Omar Lateef (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This research is aimed at the challenges of leading distributed teams in Erbil, Kurdistan, and suggests solutions. This study employed a quantitative case study methodology to examine remote work policies and methods in a company in Erbil, Kurdistan. A random sample of team members and leaders with at least six months of remote work experience from various private businesses in Erbil was surveyed using 120 questionnaires, yielding 112 completed responses. The findings of the research revealed that all three research hypotheses were supported. H1 stated that limited access to technology is a significant challenge in leading remote teams and implementing and has positive influence on the strategies for success, and the results confirmed this. Similarly, H2, which focused on communication barriers as a significant challenge and has positive influence on the strategies for success, was also supported. Lastly, H3, which emphasized the lack of trust as a challenge and has positive influence on the strategies for success, was also supported by the findings. The research demonstrated that establishing trust within remote teams in Erbil-Kurdistan was indeed a significant challenge faced by team leaders, potentially impacting the overall success of remote work strategies.